2017
DOI: 10.15207/jkcs.2017.8.2.243
|View full text |Cite
|
Sign up to set email alerts
|

A Convergence Study on the Relationship between Perfectionism, Stress, and Burnout among College Golf Athletes

Abstract: The purpose of this study was to investigate the relationship among perfectionism, stress, and burnout in college golf athletes. Participants were 221 college students. Self-oriented perfectionism and socially prescribed perfectionism were found to be the antecedent variables causing stress. Self-oriented perfectionism reduced personal accomplishments, and socially prescribed perfectionism increased the level of burnout. Additionally, perceived stress not only engendered emotional exhaustion but also reduced p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Correlation (r) MPS [5] ABQ [17] Article Bum (2017) [34] (Individual) 221 male and female golf athletes from six universities in Korea Correlation (r) K-MPS [5] MBI [22] Article So (2011) [35] (Individual, team) 271 male and female athletes in middle and high schools in Korea Correlation (r) MPS [5] MBI [22] Article Kim (2017) [36] (Individual) 165 athletes in male and female business badminton teams in Korea as of 2016…”
Section: Type Of Publicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Correlation (r) MPS [5] ABQ [17] Article Bum (2017) [34] (Individual) 221 male and female golf athletes from six universities in Korea Correlation (r) K-MPS [5] MBI [22] Article So (2011) [35] (Individual, team) 271 male and female athletes in middle and high schools in Korea Correlation (r) MPS [5] MBI [22] Article Kim (2017) [36] (Individual) 165 athletes in male and female business badminton teams in Korea as of 2016…”
Section: Type Of Publicationmentioning
confidence: 99%
“…Forest plot of the total data.Figure 2. Forest plot of the total data[12,[23][24][25]27,28,[31][32][33][34][35][36][37][38].…”
mentioning
confidence: 99%
“…Perfectionism is a personality trait characterized by striving toward flawlessness and setting excessively high standards for performance [1]. There have been several studies about perfectionism in Korean athletes [2,3]. Yoon and Kim [2] reported that the traits of perfectionism in man-to-man sports were higher than those in record genre sports.…”
Section: Introductionmentioning
confidence: 99%
“…Yoon and Kim [2] reported that the traits of perfectionism in man-to-man sports were higher than those in record genre sports. Bum et al [3] reported that self-oriented perfectionism and socially prescribed perfectionism would aggravate the level of stress and emotional exhaustion. In addition, perfectionism can arise from coach and parental pressure, which can disrupt cognitive, emotional, and behavioral aspects of sport performance [4].…”
Section: Introductionmentioning
confidence: 99%